2006
DOI: 10.1111/j.1365-2222.2006.02624.x
|View full text |Cite
|
Sign up to set email alerts
|

Sublingual immunotherapy reduces allergic symptoms in a mouse model of rhinitis

Abstract: In the present study, we have established a mouse model displaying the hallmarks of allergic rhinitis using a clinically relevant allergen. Using this model, we have demonstrated that SLIT treatment is able to reduce allergic symptoms in a time- and dose-dependent manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
50
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 39 publications
10
50
2
1
Order By: Relevance
“…The s.l. route is also effective and efficient for allergen-specific immunotherapy (7,8). Recently, we demonstrated that s.l.…”
mentioning
confidence: 99%
“…The s.l. route is also effective and efficient for allergen-specific immunotherapy (7,8). Recently, we demonstrated that s.l.…”
mentioning
confidence: 99%
“…30,31 The number and severity of systemic side effects for SLIT are much lower compared to SCIT and it has shown significant clinical efficacy compared to placebo. 14,32,33 It has been demonstrated in many clinical studies 34,35 and animal models of allergic diseases 36,37 that the effect of SLIT, both clinical and immunological, depends on the individual allergen dose given with each administration. Concomitantly with an increased efficacy, the number and severity of adverse events also increase with dose.…”
Section: Discussionmentioning
confidence: 99%
“…Brimnes et al established a mouse model using a clinically relevant allergen to produce hallmarks of allergic rhinitis. 141 Using this model, SLIT was demonstrated to reduce allergic symptoms in a time and dose-dependent manner.…”
Section: Oralmentioning
confidence: 99%